Measurement of nitrogen dioxide and nitrous acid using gas-permeable liquid core waveguides - Milani, Marcio R. [UNESP]; Dasgupta, Purnendu K. (Elsevier, 2001)
Nitrogen dioxide is an important atmospheric contaminant, classified as a criteria pollutant in the United States. It can be sensitively determined by the simple colorimetric Griess-Saltzmann method. This can constitute the basis of an inexpensive sensitive instrument based on gas-permeable liquid core waveguide tubes that allow long path absorbance measurement. Nitrous (HONO) acid is often present in the atmosphere along with NO2. Nitrous acid concentration can be significant relative to NO2, especially at night-time when photodecomposition of HONO is no longer operative. Griess-Saltzman chemistry cannot differentiate between HONO and NO2. In the present paper, we have explored the possibility of simultaneously determining both analytes by using more than one collector with dimensional differences. Presented results show that differences in either length or wall thickness can permit such differentiation. © 2001 Elsevier Science B.V.
Keywords: Nitrogen dioxide; Nitrous acid; Photodecomposition